Risk Assessment and Degradation of an Insecticide (Chlorpyriphos): A Decontamination Study under Different Culinary Processes in/on Cabbage - Md. Wasim Aktar,; Dwaipayan Sengupta,; Mariappan Paramasivam,; Ashim Chowdhury, (Agriculture and Natural Resources, 2009)
Chlorpyriphos 20 EC was applied at the rate of 500 g ai. ha-1 to cabbage heads and the samples harvested at intervals of 0 (2 hours after application), 1 and 7 days after application. The calculated half-life value and safe waiting period (8.75 and 45.29 days, respectively) indicated its persistence. Thus, to reduce the safe waiting period, efforts were made to decontaminate the chlorpyriphos residue from the cabbage head by various household preparations (viz. washing, cooking, washing plus cooking, salt water dipping, dipping in boiled salt water, dipping in detergent solution and dipping in boiled detergent solution). Statistical analysis of the data using Duncan’s multiple range test revealed that various household processing treatments substantially reduced the residue of chlorpyriphos in cabbage heads by a range of 27.89-73.32% but none were able to satisfactorily reduce the residue to below the tolerance level of 0.05 mg kg-1.